Preliminary study composition of bat species in University of Technology Mara (UiTM) Kuala Pilah, Negeri Sembilan, Malaysia / Mohamad Azam Akmal Abu Bakar and Mohd Fadhil Faudzi - Abu Bakar, Mohamad Azam Akmal; Faudzi, Mohd Fadhil (Universiti Teknologi MARA Cawangan Pahang, 2019)
South-East Asia has one of the greatest distributions of bats in this world. The deep understanding of bat diversity can be a new cognizance and an eye-opener for conserving an ecological balance in our ecosystem. However, awareness relating to the bat species especially their composition and biodiversity in University of Technology MARA (UiTM) Kuala Pilah, Negeri Sembilan is insufficient. Therefore, a preliminary study of bat composition at study sites in UiTM Kuala Pilah, Negeri Sembilan was conducted. It was conducted for two months of sampling to trap and to determine the species of the organism. Fifteen individuals from three species representing two families namely Pteropodidae and Vespertilionidae were caught using mist nets. The most common caught bat in this study was Cynopterus brachyotis(n=9) followed by Scotophillus kuhlii (n=4), and Macroglossus minimus(n=2). Since there is no research on bat studies has ever been conducted in UiTM Kuala Pilah, this study will become the beginning and starting point for bat diversity studies. In addition,this study was conducted to assess the species and diversity of organisms at UiTM Kuala Pilah. The findings of this study show that UiTM Kuala Pilah is rich in biodiversity with precious fauna and can provide a vital basic information to help in creating awareness on the importance of preserving our forests